Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.2166/hydro.2002.0013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative application of artificial neural networks and genetic algorithms for multivariate time-series modelling of algal blooms in freshwater lakes

Abstract: The paper compares potentials and achievements of artificial neural networks and genetic algorithms in terms of forecasting and understanding of algal blooms in Lake Kasumigaura (Japan). Despite the complex and nonlinear nature of ecological data, artificial neural networks allow seven-days-ahead predictions of timing and magnitudes of algal blooms with reasonable accuracy. Genetic algorithms possess the capability to evolve, refine and hybridize numerical and linguistic models. Examples presented in the paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 21 publications
(18 reference statements)
1
28
0
Order By: Relevance
“…Similar conclusions on the variables affecting algal bloom modeling has been arrived at by other researchers, for example, Recknagel et al (2002), Bobbin and Recknagel (1999), Lee et al (2003) and Muttil and Lee (2005). Figure 4 shows the plot of prediction obtained with model 10 in Table 5 (presented as Eq (7) above) and the actual Chy t+14 .…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Similar conclusions on the variables affecting algal bloom modeling has been arrived at by other researchers, for example, Recknagel et al (2002), Bobbin and Recknagel (1999), Lee et al (2003) and Muttil and Lee (2005). Figure 4 shows the plot of prediction obtained with model 10 in Table 5 (presented as Eq (7) above) and the actual Chy t+14 .…”
supporting
confidence: 81%
“…Recknagel et al (1997) did a study on predictive potential of phytoplankton models by ANN and compared with other models such as AD HOC inductive models and found that predictive accuracy improved with increased event and time resolution of data. Recknagel et al (2002) compare the potential of ANN and GA in terms of forecasting and understanding of algal blooms in Lake Kasumigaura, Japan and found that models evolved by GA performs better than ANN models and provide more transparency for physical explanation as well. Lui et al (2007) studied modeling of algal bloom with vector autoregressive model with exogenous variables in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, machine learning algorithms like the artificial neural networks (ANNs) [67,[76][77][78], and genetic algorithms (GA) [76,79] have gained momentum in water quality monitoring studies. [41] pointed out that these technique generally yields the best parameter estimates in the data set with the least amount of missing data.…”
Section: Computer Application In Data Treatmentmentioning
confidence: 99%
“…These include artificial neural networks (Recknagel et al 1997(Recknagel et al , 2002Yabunaka et al 1997;Maier et al 1998;Scardi & Harding 1999;Karul et al 2000;Jeong et al 2001;Scardi 2001;Wei et al 2001;Lee et al 2003), evolutionary based techniques (Bobbin & Recknagel 2001;Recknagel et al 2002;Jeong et al 2003;Chau 2005;Muttil & Lee 2005), fuzzy and neuro-fuzzy techniques (Maier et al 2001;Chen & Mynett 2003), and so on. DM techniques with the goal of "description" have also been used, but to a lesser extent.…”
Section: Introductionmentioning
confidence: 99%